Colleges and schools-College of Science and Mathematics-Biology-0212
Horse and Wagon Drive, Kearney Park, Fresno< California. The Largest Planting of Araucaria Bidwillii, native to the Rain Forest of Queensland Thriving in the Arid Environment of the San Joaquin Valley, of California. The Two Row Planting Was made in 1892. The Araucarias are Interspeared with Canary Island Palm, Phoenix canariesnsis.